Long-term space changes after premature loss of a primary maxillary first molar - Yng-Tzer J. Lin; Yai-Tin Lin (Elsevier, 2017)
Background/purpose: The consequence of premature loss of primary teeth resulting in the need for space maintainers has been controversial for many years. There is no longitudinal long-term report in literature regarding the premature loss of a primary maxillary first molar. The aim of this study was to continue observing the long-term space changes of 19 cases following premature loss of a primary maxillary first molar during the transition from primary to permanent dentition. Materials and methods: Ten of the 19 original participants were excluded because of extensive decay or loss to follow-up. Nine children (mean age at time of tooth extraction, 6.0 ± 0.42 years) with unilateral premature loss of a primary maxillary first molar were examined. Maxillary dental study casts were obtained 2 days or 3 days after tooth removal and, on average, 81 months later. The contralateral intact primary molars in each participant served as controls. The arch width, arch length, intercanine width, intercanine length, and arch perimeter of each study cast from the initial and follow-up examinations were measured and compared using paired t-tests. Results: Eight of nine cases (88.9%) did not show crowded permanent successors or canine block-out at the extraction site. Interestingly, the permanent dentition was more crowded at the control site (2/9) than at the extraction site (1/9). The arch width, arch length, intercanine width, and intercanine length significantly increased at 81 months (P < 0.05), whereas the arch perimeter increases approached significance (P = 0.071). Conclusion: The anterior and posterior arch dimensions significantly increased 81 months after premature loss of a primary maxillary first molar, which suggested that space maintainers were not needed in these cases.